Perspectives on the Impact, Mission and Purpose of the Business School - Eric Cornuel; Howard Thomas; Matthew Wood (Routledge, 2023)
With contributions from some of the leading thinkers in business school education, this book explores the impact and purpose of the business school, and addresses some of the most important questions facing management education today. The diverse perspectives brought together by the EFMD in this volume examine a number of common questions, themes and challenges. These include: whether business schools should be viewed as schools of management, given the complexity of the business environment; what is the positive impact of business school research, and the balance of relevant, practical impact and academic rigour; the strategic evolution of business schools and how they may evolve in a more purposeful direction; and why business school leaders compete strongly but are reluctant to collaborate, and how collaboration may encourage greater positive societal impact. With insightful commentary and illustrative case studies, this book serves as a landmark publication on the value and impact of business schools. The book will be of particular interest to those working in business schools, higher education leaders, policy makers and business leaders seeking insight into the value, impact and future of business and management education.
Keywords: 300; Business schools; Management education; Management impact; Research assessment; Responsible management